Social outcomes of community-based rangeland management in post-socialist Mongolia: influential factors and favorable institutional designs - Ulambayar, Tungalag, author; Fernandez-Gimenez, Maria, advisor; Galvin, Kathleen, committee member; Vaske, Jerry, committee member; Reid, Robin, committee member (Colorado State University. Libraries, 2015)
Community-based rangeland management (CBRM) has been proposed as a promising option to reduce rural poverty and resource degradation in post-socialist Mongolia. To date, research on CBRM in Mongolia has been limited to small samples and case studies within one or two ecological zones. Results have been mixed, with some studies showing favorable outcomes and others no effect or negative impacts of CBRM. Few studies have directly compared the outcomes of formally organized CBRM with management by traditional herder neighborhood groupings, or attempted to identify the causal mechanisms that explain variations in CBRM outcomes. Using data from 142 pastoral groups and 706 member households across 36 counties (soum) in four ecological zones, I assessed social outcomes of CBRM organizations in comparison with non-CBRM groups, explored causal mechanisms underlying these social outcomes, and examined the effects of external facilitation on institutional design of formal CBRM organizations. I found that formal groups had more information sources, stronger leadership, greater knowledge exchange, cooperation and more rules. Members of formal groups were more proactive in addressing resource management issues and used more rangeland practices than traditional neighborhoods. However, the two types of groups did not differ on most livelihood measures and had a weak difference in social capital. Four factors, access to diverse information sources, leadership, knowledge exchange and resource management rules, significantly facilitated the effect of formal organization on pastoralists’ traditional and innovative rangeland practices, proactive behavior and social networks. Importantly, information diversity had a triggering effect on other three mediating variables creating a sequential chain of information diversity → leadership → knowledge exchange → rules. This ordered chain of four mediators explains the mechanisms through which formal organization leads to comparatively greater social outcomes. I also found that these mediated effects on members’ proactive behavior and social networking varied among ecological zones. Donor facilitation approach significantly influenced CBRM group attributes and external environments, but did not affect institutional arrangements. Small group size, homogeneous interests, and heterogeneity of well-being predicted higher levels of intermediate outcomes including information diversity, leadership, and income diversity. Institutional arrangements such as the presence of sanctions, group-devised rules, frequent meetings, and recording documents increased cooperation, rules and information diversity. Similarly, access to training and local government support provided a favorable external environment for achieving intermediate outcomes. Regarding ultimate social outcomes, group characteristics such as dependence on livestock, homogeneity of interests and leader legitimacy were critical for increasing social capital, livelihoods, rangeland practices, and proactive behavior. Frequent meetings of group leaders had the greatest influence on ultimate social outcomes. Local government support and ongoing donor support were associated with increased trust and norms of reciprocity, rangeland management practices, proactiveness, and per capita livestock holdings. Overall, group attributes and external environment had a greater influence on social outcomes of pastoral CBRMs in Mongolia than institutional arrangements. I found strong evidence that formal CBRM is leading to increased social outcomes across Mongolia. Many CBRM facilitation strategies were shown to be adequate for fostering social outcomes of the pastoral groups. Early achievements of individual household level variables such as rangeland practices and behavior appeared to be “fast” variables that respond quickly to new institutions. In contrast, building social capital and reaching livelihood improvement may be “slow” variables that require time and larger scale changes. Globally, the promising case of CBRM in Mongolia may encourage mobile pastoral communities elsewhere to cooperate on the sustainable management of their resources. However, as this study showed, careful facilitation is needed to achieve intermediate outcomes, and consideration of the distinct dynamics of local resource systems is a necessary prerequisite for achieving increased social outcomes.